High-resolution genome-wide mapping of HIF-binding sites by ChIP-seq - Schödel, Johannes; Oikonomopoulos, Spyros; Ragoussis, Jiannis; Pugh, Christopher W; Ratcliffe, Peter J; Mole, David R (Blood, 2011)
Hypoxia-inducible factor (HIF) regulates the major transcriptional cascade central to the response of all mammalian cells to alterations in oxygen tension. Expression arrays indicate that many hundreds of genes are regulated by this pathway, controlling diverse processes that in turn orchestrate both oxygen delivery and utilization. However, the extent to which HIF exerts direct versus indirect control over gene expression together with the factors dictating the range of HIF-regulated genes remains unclear. Using chromatin immunoprecipitation linked to high throughput sequencing, we identify HIF-binding sites across the genome, independently of gene architecture. Using gene set enrichment analysis, we demonstrate robust associations with the regulation of gene expression by HIF, indicating that these sites operate over long genomic intervals. Analysis of HIF-binding motifs demonstrates sequence preferences outside of the core RCGTG-binding motif but does not reveal any additional absolute sequence requirements. Across the entire genome, only a small proportion of these potential binding sites are bound by HIF, although occupancy of potential sites was enhanced approximately 20-fold at normoxic DNAse1 hypersensitivity sites (irrespective of distance from promoters), suggesting that epigenetic regulation of chromatin may have an important role in defining the response to hypoxia.